H Hubungan Pengetahuan Tentang Covid-19 Dengan Perilaku Penerimaan Vaksin Pada Lansia Di Puskesmas Patuk 1 Wonosari Yogyakarta - Nessy Anggun Primasari; Erika Nurwidiyanti; Alexius Krisbianto (LPPM Universitas Sari Mulia, 2022)
Background: Coronavirus has become a serious global public health problem. This disease causes humans to start feeling from the flu to respiratory infections. Coronavirus disease so far has more often attacked the elderly and even caused severe infections and death in the elderly. The Elderly is the final stage of life that has undergone various processes of holistic change, both changes in biological, psychological, social, and spiritual aspects. Along with increasing age, the elderly are more susceptible to health problems, the Government has started the provision of COVID-19 vaccination with a priority target for the elderly aged over 60 years and over. Objective: To identify the relationship between knowledge about COVID-19 and the behavior of receiving vaccines in the elderly at the Patuk 1 Health Center Wonosari Yogyakarta. Methods: This research is a quantitative study with a cross-sectional design. A sample of 133 respondents was selected using the random sampling technique. Data on the knowledge of COVID-19 and the behavior of respondents' vaccine reception were collected using a questionnaire and analyzed by using the Spearman test. Results: The results showed that knowledge about COVID-19 (71.4%) was in the good category, (24.1%) was in the sufficient category, (4.5%) was in the poor category. Vaccine Acceptance Behavior in the category of willing to receive vaccines as many as 119 respondents (89.5%), in the category of not wanting to receive vaccines as many as 19 respondents (10.5%). Sperm test on knowledge of COVID-19 and behavior of vaccine reception showed a p value = 0.002 (p <0.05) and a correlation coefficient value of 0.263. Conclusion: There is a significant relationship between knowledge about COVID-19 and the behavior of receiving vaccines in the elderly at the Patuk 1 Health Center Wonosari Yogyakarta.